Case report: Hand-arm vibration syndrome in a dental technician - Lam, Jonathan Wen Yu; Lo, Yew-Long; Fong, Yuke Tien (Frontiers in Public Health, 2024)
Occupational exposure to vibration using hand-held tools may cause hand-arm vibration syndrome (HAVS) among workers. We report the case of a 39-year-old lady with a 5-year work exposure to repetitive wrist movements and vibration from hand tools in the dental fabrication laboratory, working as a dental technician. She presented with a 3-year history of chronic pain over the wrists and positive symptoms of numbness and tingling in the hands, pain and discomfort of the fingers during cold exposure, and poor grip strength. Symptoms over the right hand were worse than the left. She is right-hand dominant. She had bilateral median nerve neuropathy at the wrist. Nerve conductive tests were consistent with minimal bilateral carpal tunnel syndrome. MRI showed evidence of soft tissue damage from repetitive strain injury of the right wrist. Neurosensory grading for hand-vibration syndrome (HAVS) using the Stockholm Workshop Scale (SWS) was performed and she was graded as Stage 1SN with numbness or tingling symptoms. Using the International Consensus Criteria (ICC) grading for HAVS, she was graded Stage N1 with numbness and/or tingling (symptoms) of finger. A workplace risk health assessment (WHRA) was performed, and exposure scores for her work tasks in dental fabrication and risk levels were determined using the HSE (Health and Safety UK) Assessment of Repetitive Tasks (ART) tool. The processes of teeth setting using dental burs (exposure score 23), divestment work with stone clippers (score 20), and use of pneumatic drills (score 21) were deemed high-risk activities for repetitive strain injury. The use of carving tools (score 12), packing with the use of flask clamps, and trimming (score 14) were classified as medium high-risk activities for repetitive strain injuries. Workplace modifications and workplace vibration exposure level monitoring protocols were subsequently established with the stabilization of the patient’s symptoms.